2020
DOI: 10.1021/acs.jpcc.0c01149
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized Magnetic Resonance of Exchangeable Protons Using Parahydrogen and Aminosilane

Abstract: Efficient, room temperature hyperpolarization of exchangeable solvent protons combining parahydrogen (p-H 2 ), aminopropyldiethoxymethylsilane (APDMS), and IrCl(COD)-(IMes) to generate an active aminosilane−iridium complex broadens the capabilities of signal amplification by reversible exchange (SABRE)-type hyperpolarization of protons. A primary pool of hyperpolarized exchangeable protons transfers its hyperpolarization to cosolutes with labile protons, partly overcoming the catalytic specificity of SABRE-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Theo bservation of direct SABRE polarization of amines [105] and carboxylates,s uch as acetate [106] and pyruvate, [107] via complexes such as [Ir(H) 2 (IMes)(NH 2 CH 2 Ph) 3 ]Cl and [Ir(H) 2 (IMes)(py) 2 (CO 2 CH 3 )] and [Ir(H) 2 (IMes)-(DMSO)(CO 2 COCH 3 )provides confidence that the SABRE hyperpolarization of amino acids is indeed viable through N, O-, or N,O-ligation modes. [108] Therefore,not surprisingly,an early study on SABRE by Appelt and co-workers [109] suggested that all of the proteinogenic amino acids could be hyperpolarized in this way.T hey used [Ir(COD)(PCy 3 )(py)]-[PF 6 ]a st he SABRE catalyst precursor in [D 4 ]MeOH. The measurements were carried out with ah ome-built NMR spectrometer at proton frequencies of 166 kHz and 10 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Theo bservation of direct SABRE polarization of amines [105] and carboxylates,s uch as acetate [106] and pyruvate, [107] via complexes such as [Ir(H) 2 (IMes)(NH 2 CH 2 Ph) 3 ]Cl and [Ir(H) 2 (IMes)(py) 2 (CO 2 CH 3 )] and [Ir(H) 2 (IMes)-(DMSO)(CO 2 COCH 3 )provides confidence that the SABRE hyperpolarization of amino acids is indeed viable through N, O-, or N,O-ligation modes. [108] Therefore,not surprisingly,an early study on SABRE by Appelt and co-workers [109] suggested that all of the proteinogenic amino acids could be hyperpolarized in this way.T hey used [Ir(COD)(PCy 3 )(py)]-[PF 6 ]a st he SABRE catalyst precursor in [D 4 ]MeOH. The measurements were carried out with ah ome-built NMR spectrometer at proton frequencies of 166 kHz and 10 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, these restrictions are being lifted through the use of relayed polarization transfer (SABRE‐Relay) [37–42] which allows polarization of molecules such as alcohols, [38] sugars, [39] silanols [40] and others [41] without their direct ligation to iridium. Similarly, the hyperpolarization of weakly donating O‐donor molecules such as pyruvate [43] and acetate [44] has been demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…Die direkte SABRE-Polarisation von Aminen [105] und Carboxylaten wie Acetat [106] und Pyruvat [107] [108] Es überrascht daher nicht, dass eine frühe SABRE-Arbeit von Appelt et al [109] [105] Solche Komplexe kçnnen die austauschbaren Protonen dieser Reagenzien hyperpolarisieren (Abbildung 10). Sobald sie sich mit einem zweiten Molekülv erbinden, kann die Hyperpolarisation auf dieses übertragen werden.…”
Section: Angewandte Chemieunclassified